Keahlian Eksternal dan Kesuksesan Sistem ERP - Winarno, Wahyu Agus (JURNAL EKONOMI AKUNTANSI DAN MANAJEMEN, 2010)
Enterprise Resource Planning (ERP) systems is a packaged business software system that enables a company to manage the efficient and effective use of resources and providing a total integrated solution for the organizations information-processing needs. But, ERP systems success own is not easily to be reached. Because ERP software is not something that while is assembled/ implementation gets to walk success by itself. This study examine antecedent factor that influence ERP systems success. One construct that influence ERP systems success are external expertise that devide consultant effectiveness and vendor support. The sampling technique applied is convenience sampling and this research data is gathered primary data with mail survey. Questionaire was sent to go to firm that already apply ERP systems at East Java Province. Hypothesis testing is done by use of Structural Equation Modeling (SEM) approach by use of software Partial Least Square (PLS). The Result of this research indicates that vendor support have positive affect to ERP systems success. In other hand, effectiveness consultant not affect to ERP systems success. Keywords: ERP, ERP systems success, vendor support, consultant effectiveness, Partial Least Square (PLS).